2008
DOI: 10.1063/1.2829896
|View full text |Cite
|
Sign up to set email alerts
|

X-ray analysis of the magnetic influence of oxygen in Pt∕Co∕AlOx trilayers

Abstract: X-ray spectroscopy measurements have been performed on a series of Pt∕Co∕AlOx trilayers to investigate the role of Co oxidation in the perpendicular magnetic anisotropy at the Co∕AlOx interface. It is observed that varying the degree of oxidation modifies the magnetic properties of the Co layer, inducing a magnetic anisotropy crossover from in plane to out of plane. The microscopic structural properties are analyzed via x-ray photoelectron spectroscopy measurements. It is shown that increasing the oxidation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 22 publications
4
60
1
Order By: Relevance
“…Experiments were performed on a 0.6 nm thick Co film sandwiched between 3 nm Pt and 1.6 nm Al layers deposited by sputtering on a thermally oxidized Si wafer. The top Al layer was exposed to an oxygen radio-frequency plasma resulting in a fully oxidized AlO x interface at the Co boundary [86,87]. SIA results from the presence of AlO x and Pt on either side of the Co layer, where Pt/Co hybridization enhances atomic SO coupling and both interfaces create a strong out-of-plane electron potential gradient.…”
Section: (D) Spin-orbit Torques In Ultrathin Metal Filmsmentioning
confidence: 99%
“…Experiments were performed on a 0.6 nm thick Co film sandwiched between 3 nm Pt and 1.6 nm Al layers deposited by sputtering on a thermally oxidized Si wafer. The top Al layer was exposed to an oxygen radio-frequency plasma resulting in a fully oxidized AlO x interface at the Co boundary [86,87]. SIA results from the presence of AlO x and Pt on either side of the Co layer, where Pt/Co hybridization enhances atomic SO coupling and both interfaces create a strong out-of-plane electron potential gradient.…”
Section: (D) Spin-orbit Torques In Ultrathin Metal Filmsmentioning
confidence: 99%
“…The latter can significantly influence the PMA. For example, experiments performed in a similar Co/AlO x system 33,34 have shown that the PMA of the Co film is likely to originate from the presence of a CoO x layer at the interface. In the section 'Fundamental understanding of Magnetoelectric coupling", we will briefly discuss how DFT modeling can be utilized to gain insights between the degree of interfacial oxidation and the PMA along with the challenges.…”
Section: Introductionmentioning
confidence: 99%
“…2 More specifically in these kinds of nanostructures, a perpendicular magnetic tunnel junction implies two electrodes of ferromagnetic layers inserting an oxide one. Previous studies [3][4][5] reported a change of the magnetic anisotropy from in-plane to out-of-plane at room temperature (RT) for Si/SiO 2 /Pt(3 nm)/Co(0.6 nm)/Al(1.6 nm) þ t Ox either for efficient oxidation times values (namely t Ox ), or by increasing the annealing temperature (namely T Ann ) of the trilayer. Such change seems to be related to the diffusion of the oxygen, induced by the annealing (via T Ann ) and/or the quantity of oxygen (via t Ox ), toward the Co/AlO x interface.…”
mentioning
confidence: 99%
“…In other words, the Co-Al bonds would be replaced by Co-O ones due to the annealing and/or the oxidation time. 4,6 However, the dependencies of the magnetic properties as a function of deposition parameters are not completely understood, especially at low temperature. Also, various structural schemes can be at the origin of improved PMA: oxygen at the interfaces between Co and AlO x , Co-Pt intermixing, or chemical modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation